The Public Relation Strategies Of Blitar Regency Diskominfo For The Smart City Program - Fandi Avista Baihaqi Zein; Bambang Setyo Utomo (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study aims to analyze the public relations strategies of the Blitar Regency Communication and Informatics Office (DISKOMINFO) in socializing the Smart City Program. It addresses the limited academic focus on PR strategies in PR strategies in non-metropolitan contexts, particularly in the implementation of smart program initiatives. Using a qualitative case study method, data were collected through semi-structured interviews, participant observation, and document analysis. The findings were categorized based on Ruslan’s five strategies: operational, persuasive-educative, social responsibility, collaborative, and coordinative-integrative. Each strategy was implemented adaptively to align with local conditions, promote public awareness, and build institutional collaboration. The results show that operational and persuasive approaches were dominant, while collaboration efforts required better implementation. This research contributes to understanding how local governments could effectively apply strategic communication to support digital transformation programs.